Computational schemes on the bending fatigue deformation and damage of three-dimensional orthogonal woven composite materials - Sun, Baozhong; Wang, Jinhua; Wu, Liwei; Fang, Fang; Gu, Bohong (Computational materials science, 2014)
[Display omitted] •Fatigue behavior of 3D orthogonal woven composites (3DOWC) is studied at microstructure level.•Fatigue damage and degradation were revealed with numerical analyses.•The influences of the microstructure on the fatigue behaviors have been analyzed. This paper reports a computational scheme on three-dimensional orthogonal woven composites (3DOWC) fatigue behavior under three-point low-cycle bending. Based on three-point cyclic bending fatigue tests, a microstructure model was established at yarn level for predicting the fatigue behaviors. The stiffness degradation and damage morphologies of the 3DOWC were obtained from finite element analysis (FEA) and compared with those from experimental. The stress distribution, energy absorption and damage morphologies in the different parts of the 3DOWC sample were obtained to analyze fatigue failure mechanisms. The influences of warp yarns, weft yarns and Z-yarn systems were discussed. It is found that warp yarn system bears the most cyclic load as well as energy absorption. The stress concentration area was located in the central loading area, especially in the warp yarns that is close to the Z-yarns side and its channels. The triangle damage area was gradually generated from up to down in the stress concentration area as the loading cycle increased.